Comparison of high pressure processing with chemical method to characterize astaxanthin profile from various species of shrimp carapace - Irna, Cicy; Jaswir, Irwandi; Othman, Rashidi; Jimat, Dzun Noraini (2015)
Astaxanthin is one the main carotenoid pigment. It has beneficial effects on the immune system of human body due to powerful antioxidant properties. The application of those bioactive compounds are significant found in food, pharmaceutical and cosmetic industries. The goal of this research was to investigate the profile from various species Malaysian shrimp carapace. There were six types of shrimp species studied: Parapenaeopsis sculptili, Metapenaeus lysianassa, Macrobrachium rosenbergii, Metapenaeopsis hardwickii, Penaeus merguiensis and Penaeus monodon were used to investigate carotenoid and astaxanthin content. The investigation was driven using High Pressure Processing (HPP) and chemical method. The effects of HPP at 210 MPa for pressure within 10 min with a mixture solvents of acetone and methanol (7:3, v/v). HPP was proven to have a significant impact to increase the content for carotenoid and astaxanthin. The highest number of carotenoid and astaxanthin content is contained in Penaeus monodon species. The increased of carotenoid and content using HPP were 21.31 ug and 8.362 ug/g. The comparison between the HPP and chemical method showed that HPP has advantage advantages with higher content of astaxanthin in a shorter time. Hence, the use of HPP to increase carotenoid and astaxanthin from various species of shrimp carapace is a potential alternative to chemical method.